BIOM-54. ANALYTICAL VALIDATION OF A TARGETED GENE EXPRESSION BIOMARKER PREDICTING MENINGIOMA OUTCOMES AND RADIOTHERAPY RESPONSES. (14th November 2022) - Chen, William; Lucas, Calixto-Hope; Choudhury, Abrar; Vasudevan, Harish; Magill, Stephen; Raleigh, David
Abstract: BACKGROUND: Improvements in meningioma risk stratification are needed to guide postoperative management. We previously developed and externally validated a targeted gene expression biomarker predicting meningioma outcomes and radiotherapy response using fresh frozen meningiomas. Here, we present the analytical validity, test-retest and cross-platform reproducibility, intra-tumor heterogeneity, and formalin fixed paraffin embedded (FFPE) concordance for this biomarker. METHODS: Matched FFPE and fresh frozen samples from 50 meningiomas underwent RNA extraction for concordance testing using a custom Nanostring gene expression panel comprised of 34 meningioma genes and 7 housekeeping genes. Matched Nanostring gene expression profiling and RNA-sequencing was available from 173 fresh frozen meningiomas. Nanostring batch, machine, and technician variability was tested on 10 FFPE meningiomas using 2 independent batches of biomarker reagents that were processed at 2 independent laboratories. To study intra-tumor heterogeneity, 68 spatially distinct meningioma biopsies obtained under stereotactic guidance from 13 tumors were analyzed using the Nanostring gene expression biomarker. RESULTS: Matched FFPE and fresh frozen meningioma samples (N=50) demonstrated high gene expression concordance (Pearson R =0.89, F-test P< 2.2e-16) and risk score concordance ( R =0.78, F-test P< 1.8e-11, residual standard error 0.12). The biomarker achieved high performance on FFPE samples (local freedom from recurrence [LFFR] c-index 0.75±SEM 0.05, 5y LFFR AUC 0.84, 95% interval 0.67-0.96). Test-retest concordance on FFPE samples (N=10) across independent reagent batches, machines, and technicians was high (gene expression concordance: R =0.97; risk score concordance R =0.94). Transcript counts were concordant across Nanostring and RNA sequencing approaches (N=173 frozen samples, R =0.90). Stereotactic intra-operative sampling (N=68 samples from 13 patients) revealed low levels of intra-tumor heterogeneity (median inter-quartile risk score within tumor: 0.10±0.01). CONCLUSIONS: We demonstrate analytical reproducibility and robustness of a gene expression biomarker predicting meningioma outcomes and radiotherapy responses in FFPE and frozen samples across multiple conditions and platforms.